The impact of problem-based learning and metacognition on solving environmental pollution issues - Annisa Cahyadini; Hanum Isfaeni; Ratna Komala (University of Muhammadiyah Malang, 2024)
The lecture technique still dominates in biology education, and there are not enough hands-on, interactive, creative, and problem-solving learning activities to encourage students to apply their problem-solving skills. The purpose of this study is to examine how the problem-based learning (PBL) model and students' metacognition skills affect their ability to solve environmental pollution issues. A total of 60 X MIPA students from SMA Muhammadiyah 16 Jakarta comprised the total sample of the research, collected using the quasi-experimental approach. For the study, two groups were utilized: the experimental group (X MIPA 1) and the control group (X MIPA 2). A 2 x 2 factorial design with a pretest-posttest control group was employed for the investigation. The instruments used in the study were classified as tests or non-tests. The test instrument is an essay designed to collect data on problem-solving ability and metacognition ability, while the non-test instruments are student worksheets that refer to the PBL stage, and the observation sheet is designed for instructors and students. Data analysis using ANCOVA with a significance level of 0.000 < α = 0.05 indicates that H0 was rejected. The interaction between the PBL learning model and students' metacognition skills also has an impact on their capacity to address environmental pollution-related issues.